A 4-year-old child presenting morning onset of spontaneous tracheal rupture due to bronchial mucous plug occlusion during the nighttime sleep: a case report. (December 2016) - Capasso, Raffaella; Carbone, Mattia; Rossi, Eugenio; Mamone, Rosanna; Zeccolini, Raffaele; Reginelli, Alfonso; Zeccolini, Massimo; Brunese, Luca; Rotondo, Antonio
Abstract Background Coughing is the most efficient mechanism for clearing mucus and fluid secretions from the airways and its reflex can be suppressed by sleep. Spontaneous tracheal ruptures are believed to result from raised intratracheal pressure against a closed glottis, such as for severe coughing. This is the first reported case of tracheal rupture presented on morning awakening after bronchial mucous plug formation during the nighttime sleep because of an ineffective cough reflex. Case presentation An otherwise healthy white 4-year-old child presented morning onset of dyspnea, chest pain and diffuse swelling of the neck. His history was significant only for nonsevere coughing episodes before his nighttime rest; the child's parents denied any recent fever, weight loss, pains, trauma, bronchial asthma, and sick contacts. A chest X-ray and computed tomography scan revealed pneumomediastinum, obstructive atelectasis of the lower lobe of his left lung, and a small tracheal laceration confirmed by an emergency bronchoscopy. After endoscopic removal of a mucous plug and secretions, the child's pulmonary gas exchange and respiratory rate improved, so our patient was managed conservatively. Conclusions This report illustrates an unusual presentation of lung obstructive atelectasis due to a mucous plug manifested by tracheal rupture. This report also highlights the importance of the coughing reflex as one of several defensive mechanisms protecting the airways from the potentially damaging effects of aspirate and accumulated secretions.